Part-Scale Thermomechanical and Grain Structure Modeling for Additive Manufacturing: Status and Perspectives - Yancheng Zhang; Gildas Guillemot; Théophile Camus; Oriane Senninger; Michel Bellet; Charles-André Gandin (Metals, 2024)
Thermomechanical modeling of additively manufactured parts made by laser powder bed fusion aims to control stresses and distortions built during processing. This is, by nature, a multiscale metallurgical and mechanical problem, notably due to the strong texture of the grain structure that results from the process and may locally dictate the thermomechanical behavior law. Similarly, stresses and distortions are directly influenced by the heat transfer process at the system scale, including the consequences of the link between the part and the substrate and the weaker interactions with the powder bed and the gas environment. To achieve relevant modeling, we first demonstrate capabilities to assess at part scale, both i- the prediction of the grain structure and ii- the thermomechanical analyses. A discussion follows that summarizes the foreseen directions to achieve coupling and/or chaining between grain structure simulations and mechanical analyses at part scale.